Identification and optimization for hydraulic roll gap control in strip rolling mill - Sun, Jie; Chen, Shu-zong; Han, Huan-huan; Chen, Xing-hua; Chen, Qiu-jie; Zhang, Dian-hua (Journal of Central South University, 2015)
In order to improve the control performance of strip rolling mill, theoretical model of the hydraulic gap control (HGC) system was established. HGC system offline identification scheme was designed for a tandem cold strip mill, the system model parameters were identified by ARX model, and the identified model was verified. Taking the offline identified parameters as the initial values, online identification using recursive least square was carried out with model parameters changing. For the purpose of improving system robustness and decreasing the sensitivity due to model errors, the HGC system based on generalized predictive control (GPC) was designed, and simulation experiments for traditional controller and GPC controller were conducted. The results show that both controllers acquire good control effect with model matching. When the model mismatches, for the traditional controller, the overshot will increase to 76.7% and the rising time will increase to 165.7 ms, which cannot be accepted by HGC system; for the GPC controller, the overshot is less than 8.5%, and the rising time is less than 26 ms in any case.